Aktivitas Antioksidan Teh Daun Alpukat (Persea americana Mill) Dengan Variasi Teknik Dan Lama Pengeringan - Sari, Mei Ambar; , Dr. Nanik Suhartatik, S.TP., M.P (2015)
Tea was a non alcoholic drinks that made from tea leaves with certain treatment processes. Tea contains many compounds that were beneficial to health. Currently the product of tea many developments, tea is not only made from tea leaves but also can be made of avocado leaves. Avocado leaves contain of flavonoids, saponins, tannins, alkaloids, and polysaccharides. Flavonoids were one of antioxidant was compounds that function as free radical scavenger. The purpose of this research to determine the antioxidant activity and organoleptic quality of avocado leaf tea with a variety of techniques and drying time. This research used a completely randomized design 2 factors. Factor 1: Mechanical drying: sun-dried (T1), basketball-fired (T2), oven-dried (T3). Factor 2: drying time: 2 hours (U1), 2.5 hours (U2), 3 hours (U3) with 3 replications. The results showed that the highest antioxidant activity of the formulation (T3U1) technique oven-dried 2-hour drying time which is 85.11% and the lowest antioxidant activity in the formulation (T1U3) sun-dried technique drying time 3 hours ie 58.64%. Organoleptic quality test showed that the avocado leaf tea has a light brown color dominance, taste slightly bitter, slightly unpleasant scent, and low acceptance.